Water-soluble filament in multifilament approach for ultrasound phantom fabrication (Transactions on Additive Manufacturing Meets Medicine, 2024)
Ultrasound phantoms are used in research, equipment testing, calibration, and even in the field of medical training. Despite their importance, commercial ultrasound phantoms are often expensive and may not meet user requirements. While simplistic phantom construction methods exist which use readily available materials, they often lack versatility in both their exterior and interior designs. By using tissue-mimicking materials such as gelatin, agarose, or polyvinyl alcohol mixed with water, simple yet effective ultrasound phantoms can be created through a heating and hardening process. While designing the outer structure of these phantoms can be achieved through the creation of various molds, crafting complex inner structures poses a more difficult task. Additive manufacturing, specifically fused deposition printing with standard 3D printers, presents a promising solution to this challenge. This involves using soluble materials that can be removed after the phantom hardens. In prior research, we successfully demonstrated this methodology using high impact polystyrene and VXL70. Building on this, our current study aims to simplify the process and evaluate non-toxic, water-soluble filaments. Using polyvinyl alcohol filament in combination with high impact polystyrene is a promising approach. These phantoms serve versatile purposes, including the replication of vascular structures or the incorporation of distinct material regions to simulate tumor structures. Through this investigation, we aim to enhance the accessibility and functionality of ultrasound phantoms for diverse research and medical applications.
Keywords: ultrasound diagnostics; medical phantom; realistic phantom; FDM